Influência do padrão de evaporação do silano sobre a resistência de união entre uma cerâmica à base de dissilicato de lítio e um cimento resinoso quimicamente ativado: avaliação in vitro através de um ensaio mecânico de microtração - Carolina Nemesio de Barros Pereira (2006)
Ceramic-bonded restoration longevity and durability are related with the quality and stability of the bond between the ceramic surface and the luting agent. Microtensile bond strength values have been used to predict the clinical success of these restorations. With the aim to evaluating the influence of silane heat treatment on the bond strength between a ceramic and a composite chemmically activated resin cement (C&BÔ), eighteen blocks of IPS Empress®2 were fabricated, flattened (240 320-grit metallographic paper) and luted to composite resin blocks (InTen-S®) using a chemical adhesive system (Lok®). Six groups with three blocks each were analyzed according to the ceramic surface treatment: G1) no treatment; G2) HF (Hydrofluoric Acid 10%) + S (silane Monobond-S® with microbrush dried at room temperature for 3min); G3) S + rinsed + room temperature (3min); G4) S + rinsed with boiling water + room temperature (3min); G5) S + rinsed with boiling water + dried at 50±5ºC (3min); G6) S + dried at 50±5ºC (3min) + rinsed with boiling water + room temperature (3min). The ceramic / resin luted blocks were sectioned in sticks 7 days after the cementation procedure and stored in water for 30 days until microtensile test were performed (0,5mm/min). A device to attach the sticks by their top and buttom surfaces, instead of at the lateral surface was developed. All the specimens of G1 debonded during the cutting procedures. Mean tensile bond strength and standard deviation values were statistically higher for G2 than for G4, statistically similar to G5, and these were higher to G3 and G6, which were statistically similar. Fracture surfaces were examined using ligth microscopy (50x), revealling that all fractures occurred within the adhesion zone. For G2, 51% were coesive fractures in the composite luting structure. One hundred percent of the fractures were adhesive for G3 and G6. The coesive failure mode was observed in G4 (24%), G2 (30%) and G5 (40%). It has being demonstraded a direct relationship between coesive failure mode and higher bond strength values. It was possible to conclude that the silane improved bond strength, being most effective when used before HF conditioning (G2).